2014
DOI: 10.1159/000358796
|View full text |Cite
|
Sign up to set email alerts
|

Vitreous Hemorrhage Caused by Ruptured Retinal Macroaneurysm

Abstract: Purpose: To report the clinical findings of 7 patients with a vitreous hemorrhage (VH) caused by a ruptured retinal macroaneurysm. Methods: Interventional case series. The medical records of 7 patients with a VH caused by a ruptured macroaneurysm and treated by either medication or vitrectomy were reviewed. The main outcome measures were the visual acuity, appearance of the fundus and optical coherence tomographic findings. Results: Two patients, aged 49 and 58 years, had retinal macroaneurysms at the optic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…1 Several studies have shown that PPV is an effective treatment method to address more complicated, severe cases of RAM with VH. 1,15 In our study, the mean ± SD time to intervention was 13 ± 15.3 days for PPV and 38 ± 69.9 days for IVI. One hypothesis is that PPV is more often recommended for moderate to severe cases with the need for a sooner return of higher level of visual acuity or prompter need to clear an obscuring VH to properly monitor the RAM in subsequent months.…”
Section: Discussionmentioning
confidence: 59%
“…1 Several studies have shown that PPV is an effective treatment method to address more complicated, severe cases of RAM with VH. 1,15 In our study, the mean ± SD time to intervention was 13 ± 15.3 days for PPV and 38 ± 69.9 days for IVI. One hypothesis is that PPV is more often recommended for moderate to severe cases with the need for a sooner return of higher level of visual acuity or prompter need to clear an obscuring VH to properly monitor the RAM in subsequent months.…”
Section: Discussionmentioning
confidence: 59%
“…These vessels are subsequently more susceptible to dilation from elevated hydrostatic pressure . When the aneurysmal dehiscence is large, it is more likely to lead to haemorrhages at all levels of the retina . Hypertensive patients are more prone to these occurrences as they experience increased hydrostatic pressure, decreased autoregulation and hyaline degeneration …”
Section: Discussionmentioning
confidence: 99%
“…In patients presenting with retinal haemorrhage and exudation, the clinician must rule out diabetic retinopathy, retinal vein occlusion, Coats' disease, radiation retinopathy, cavernous haemangioma and retinal capillary haemangiomas. Differentials for when vitreous haemorrhage is present include proliferative diabetic retinopathy, ischaemic retinal vein occlusion, retinal tear and wet age‐related macular degeneration . In these cases, the diagnosis may be complicated as the aneurysm may be obscured by blood in the vitreous.…”
Section: Discussionmentioning
confidence: 99%
“…Most common complications of RAM on the optic disc include retinal hemorrhages, retinal exudates, branch retinal artery occlusion (BRAO), and vitreous hemorrhages (VH) [ 1 , 2 , 3 , 4 , 5 ]. Although RAMs can cause VH [ 1 , 2 , 3 , 5 ], their frequency and timing of VH occurrence on the optic disc is unknown [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. To the best of our knowledge, no reports have clearly demonstrated the early onset of VH after development of RAM on the optic disc.…”
Section: Introductionmentioning
confidence: 99%